Professor Johann Dreyer: (31st December 1956 – 15th December 2020) (The Journal of Geography Education in Africa, 2021)
Professor Johann Dreyer referred to himself as “Mooi Johann”. It was fun to watch peoples’ stunned reaction as he introduced himself to them for the first time. “Mooi Johan” directly translated from Afrikaans to English would equate to “Beautiful Johann”. Their confusion and disbelief probably caused by dissonance was immediately followed by laughter and lighthearted banter as the icy barrier between strangers vapourised. He made everyone feel comfortable in his presence.